2016
DOI: 10.1371/journal.pone.0165029
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Language Use Influences Oculomotor Task Performance: Neurophysiological Evidence of a Shared Substrate between Language and Motor Control

Abstract: In the present electroencephalographical study, we asked to which extent executive control processes are shared by both the language and motor domain. The rationale was to examine whether executive control processes whose efficiency is reinforced by the frequent use of a second language can lead to a benefit in the control of eye movements, i.e. a non-linguistic activity. For this purpose, we administrated to 19 highly proficient late French-German bilingual participants and to a control group of 20 French mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…It seems that both simultaneous and successive bilinguals possess a certain ease in switching from one language to another, which necessitates mental flexibility, and to some extent also involves inhibition processes (Bobb and Wodniecka 2013;Costa and Santesteban 2004;Dijkstra and van Hell 2003;Heidlmayr et al 2016;Meuter 2005). It has been well demonstrated that language switching in bilinguals requires language control processes, and more specifically that an active top-down inhibition mechanism should be applied to refrain interference from the irrelevant language (Abutalebi and Green 2007;Aparicio and Lavaur 2013;Chauncey et al 2008;Green 1998).…”
Section: Bilingualism and Cognitive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that both simultaneous and successive bilinguals possess a certain ease in switching from one language to another, which necessitates mental flexibility, and to some extent also involves inhibition processes (Bobb and Wodniecka 2013;Costa and Santesteban 2004;Dijkstra and van Hell 2003;Heidlmayr et al 2016;Meuter 2005). It has been well demonstrated that language switching in bilinguals requires language control processes, and more specifically that an active top-down inhibition mechanism should be applied to refrain interference from the irrelevant language (Abutalebi and Green 2007;Aparicio and Lavaur 2013;Chauncey et al 2008;Green 1998).…”
Section: Bilingualism and Cognitive Controlmentioning
confidence: 99%
“…The use of more than one language is one of the exercises, amongst other activities such as playing music (Bialystok and DePape 2009), playing computer and video games (Bialystok et al 2006;Dye et al 2009), or practicing sports requiring high level of bimanual coordination (Diamond 2011) that plays a role in the strengthening of executive functions (Bialystok 2001;Bialystok et al 2006;Bialystok and DePape 2009;Costa et al 2008b;Diamond 2010;Heidlmayr et al 2014Heidlmayr et al , 2015Heidlmayr et al , 2016Kroll et al 2012). However, results are far from consensual and several studies reported a clear bilingual advantage for performing various tasks involving executive control (e.g.…”
Section: Bilingualism and Executive Functions Trainingmentioning
confidence: 99%
“…But they should also look in to oscillatory activity and their functional significance with respect to cognitive control processes. Recently there has been much progress in our understanding of the functional significance of specific frequency bands with respect to cognitive and motor control, with theta (4-7 Hz) emerging as a marker of cognitive control (e.g., Cavanagh & Frank, 2014;Hanslmayr et al, 2008;Mückschel, Stock, Dippel, Chmielewski, & Beste, 2016), alpha (8-12 Hz) as a marker of inhibition (e.g., Jensen & Mazaheri, 2010;Klimesch, 2012;Waldhauser, Johansson, & Hanslmayr, 2012), or beta (13-30 Hz) as a marker of the maintenance of the current sensorimotor or cognitive state (e.g., Engel & Fries, 2010;Heidlmayr, Doré-Mazars, Aparicio, & Isel, 2016). Fig.…”
Section: A Unified Neurocognitive Model Of the Executive Control Timementioning
confidence: 99%